Diagnosis and management of heparin‐induced thrombocytopenia: a consensus statement from the Thrombosis and Haemostasis Society of Australia and New Zealand HIT Writing Group. Issue 11 (2nd June 2019) - Joseph, Joanne; Rabbolini, David; Enjeti, Anoop K; Favaloro, Emmanuel; Kopp, Marie‐Christine; McRae, Simon; Pasalic, Leonardo; Tan, Chee Wee; Ward, Christopher M; Chong, Beng H
Abstract: Introduction: Heparin‐induced thrombocytopenia (HIT) is a prothrombotic disorder that occurs following the administration of heparin and is caused by antibodies to platelet factor 4 and heparin. Diagnosis of HIT is essential to guide treatment strategies using non‐heparin anticoagulants and to avoid unwanted and potential fatal thromboembolic complications. This consensus statement, formulated by members of the Thrombosis and Haemostasis Society of Australia and New Zealand, provides an update on HIT pathogenesis and guidance on the diagnosis and management of patients with suspected or confirmed HIT. Main recommendations: A 4Ts score is recommended for all patients with suspected HIT prior to laboratory testing. Further laboratory testing with a screening immunoassay or confirmatory functional assay is not recommended in individuals with a low 4Ts score. However, if there are missing or unreliable clinical data, then laboratory testing should be performed. A positive functional assay result confirms the diagnosis of HIT and should be performed to confirm a positive immunoassay result. Heparin exposure must be ceased in patients with suspected or confirmed HIT and initial treatment with a non‐heparin alternative instituted. Non‐heparin anticoagulants (danaparoid, argatroban, fondaparinux and bivalirudin) used to treat HIT should be given in therapeutic rather than prophylactic doses. Direct oral anticoagulants may be used in place of warfarin after patients with HIT have responded to alternative parenteral anticoagulants with platelet count recovery. Changes in management as a result of this statement: These are the first Australasian recommendations for diagnosis and management of HIT, with a focus on locally available diagnostic assays and therapeutic options. The importance of examining both clinical and laboratory data in considering a diagnosis of HIT cannot be overstated.